A Public Health Systems View of Risk Communication About Zika. (May 2020) - Kirk Sell, Tara; Ravi, Sanjana J.; Watson, Crystal; Meyer, Diane; Pechta, Laura E.; Rose, Dale A.; Lubell, Keri M.; Podgornik, Michelle N.; Schoch-Spana, Monica
Objectives: The spread of Zika virus throughout Latin America and parts of the United States in 2016 and 2017 presented a challenge to public health communicators. The objective of our study was to describe emergency risk communication practices during the 2016-2017 Zika outbreak to inform future infectious disease communication efforts. Methods: We conducted semi-structured telephone interviews with 13 public health policy makers and practitioners, 10 public information officers, and 5 vector-control officials from May through August 2017. Results: Within the public health macro-environment, extended outbreak timeframe, government trust, US residence status, and economic insecurity set the backdrop for Zika communication efforts. Limited resources, staffing, and partnerships negatively affected public health structural capacity for communication efforts. Public health communicators and practitioners used a range of processes and practices to engage in education and outreach, including fieldwork, community meetings, and contact with health care providers. Overall, public health agencies' primary goals were to prevent Zika infection, reduce transmission, and prevent adverse birth outcomes. Conclusions: Lessons learned from this disease response included understanding the macro-environment, developing partnerships across agencies and the community, and valuing diverse message platforms. These lessons can be used to improve communication approaches for health officials at the local, state, and federal levels during future infectious disease outbreaks.